2020
DOI: 10.4236/oji.2020.102003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Commercial Assays for the Detection of SARS-CoV-2 Antibodies or Antigens

Abstract: Background: COVID-19 produced by SARS-CoV-2 infection has spread worldwide. There is a growing need for immunological assays to detect viral specific antibodies or viral antigen. Current standard of diagnosis is reverse-transcriptase polymerase chain reaction (RT-PCR) in nasopharyngeal swabs. However, serological tests can be used to determine previous exposure to the virus and complement the diagnosis. IgM and IgG SARS-CoV-2 specific antibodies can be detected as early as one week after infection and assays c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Binding tests are used to determine the presence or absence of viral-specific antibodies, and levels of serum-NAbs correlate with vaccine protection [3,4]. Many different methods are widely used for antibody detection, among them enzyme-linked immunosorbent assay (ELISA) and lateral flow immunoassays (LFIAs) which are commercially available tests for SARS-CoV-2 infection [5]. Several meta-analyses have shown that ELISA and chemiluminescence (CLIA) methods for Covid-19 perform better, in terms of sensitivity and specificity, than LFIA and immunofluorescence antibody test (IFAT) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Binding tests are used to determine the presence or absence of viral-specific antibodies, and levels of serum-NAbs correlate with vaccine protection [3,4]. Many different methods are widely used for antibody detection, among them enzyme-linked immunosorbent assay (ELISA) and lateral flow immunoassays (LFIAs) which are commercially available tests for SARS-CoV-2 infection [5]. Several meta-analyses have shown that ELISA and chemiluminescence (CLIA) methods for Covid-19 perform better, in terms of sensitivity and specificity, than LFIA and immunofluorescence antibody test (IFAT) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Serological assays to measure SARS-CoV-2 specific antibodies are useful for surveillance studies and to determine the rate of exposure (6). There are different methods available including lateral flow immunochromatography (LFI), ELISA and chemiluminescence (CLIA) with a wide brand offer (7). Among other variables, serological tests can differ from antigens used for antibody detection and their performance characteristic such as sensibility and specificity (6, 8).…”
Section: Introductionmentioning
confidence: 99%